Challenges for monetary policy and its communication - Athanasios Orphanides (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2025)
The post-pandemic inflation surge underscores that monetary policy continues to be hampered by two long-standing challenges: the pretence of knowledge and the proclivity for discretion. Focusing on the Federal Reserve, this paper demonstrates how simple policy rules, designed to be robust under imperfect knowledge, can mitigate these challenges. The Fed's post-pandemic policy error-maintaining excessive accommodation as inflation pressures mounted-could have been avoided with guidance from a simple natural growth targeting rule that had been included in the Fed's Bluebook/Tealbook starting in 2004, but was not disclosed to the public in real time. Formal adoption and disclosure of such a rule can help discipline discretion and improve both the conduct and communication of monetary policy.
Keywords: E52; E58; E61; 330; Policy discretion; simple rules; natural growth targeting; inflation surge